Multiculturalism, Islamophobia and the Muslim Minority in Australia: A Reflection - Sahrasad, Herdi; Nurdin, Muhammad Amin; Dar, Mai; Baihaky, Rachmat (Journal of Al-Tamaddun, 2024)
Australia’s approach to multiculturalism has been a journey of evolving policies and societal shifts. The country’s immigration policies in the 1960s marked a significant departure from the restrictive ‘White Australia’ policy, leading to a more diverse cultural, ethnic, and religious population. Recognizing the potential for value and norm conflicts, the Australian government adopted multiculturalism as a state ideology, aiming to foster social cohesion and reduce inter-community conflicts. This policy has been largely successful in managing conflicts, as evidenced by the relatively low incidence of political, ethnic, and religious violence, including terrorism, compared to other nations. The positive impact of multiculturalism is evident in the thriving Australian Muslim communities, which, along with other ethnic and religious groups, have been able to preserve their cultural heritage. These communities contribute significantly to the social and economic fabric of the nation. However, despite the overarching success of multiculturalism, challenges persist. The Muslim minority in Australia has faced Islamophobia, manifesting in both overt attacks and subtle forms of discrimination. This has been a complex issue, with some Muslim groups maintaining a degree of exclusivity and engaging in identity politics, while also recognizing and embracing the broader multicultural ethos that has become an integral part of Australia’s identity. The Australian government has continued to refine its multicultural policies, with initiatives aimed at promoting anti-racism, access, and equity since 2010. These efforts are part of a broader commitment to diversity, belonging, and inclusion, which encompasses Aboriginal and Torres Strait Islander peoples as well. The policy landscape is complemented by state and territory policies that further support multiculturalism. Despite the progress, the experiences of Australian Muslims highlight the ongoing need for vigilance against discrimination. Reports indicate that Australian Muslims are a diverse group, facing stereotypes and prejudice that can perpetuate social tensions. The Australian Human Rights Commission has emphasized the importance of sharing the stories of Australian Muslims to foster understanding and address Islamophobia. The Commission’s findings underscore the need for a national anti-racism framework and strong leadership to combat discrimination and support social cohesion. While Australia’s multicultural policy has been a beacon of successful integration and social harmony, it is clear that the journey is not complete. The nation continues to grapple with the dual realities of a celebrated multicultural society and the undercurrents of intolerance that challenge it. The experiences of the Australian Muslim community serve as a reminder of the work that remains to be done in ensuring that multiculturalism is not just a state ideology but a lived reality for all Australians. The path forward lies in education, awareness, and institutional change that upholds the values of diversity and inclusion for every individual in the nation.